Exploring the Social and Cultural Implications of Hate Speech on Facebook in Malaysia (Sains Humanika, 2023)
The study provides insights into the prevalence of hate speech on Facebook among Malaysian users and highlights the need for greater efforts to counteract hate speech in Malaysia. Effective policies and interventions could be developed to address this issue based on the findings. This study examines hate speech trends among Facebook users in Malaysia and their attitudes towards regulating such speech. The study employs a four-part survey questionnaire: Part A covers demographics (gender, age, education); Part B examines social media engagement (platform choice, Facebook usage); Part C explores Facebook hate speech (locations, types, frequency); and Part D investigates responses (experiences, emotions, actions, perspectives). It was conducted with 225 respondents. The study found that race-related content is not the most commonly observed form of hate speech on Facebook in Malaysia; instead, users commonly encounter other types of hate speech. Additionally, users' level of awareness regarding hate speech is influenced by their level of activity on the platform. Notably, the duration of time spent on Facebook is not correlated with the frequency of exposure to hate speech. Experiences of being victimized by hate speech do not necessarily lead to support for regulating hate speech on Facebook. These findings provide valuable insights into the prevalence of hate speech on Facebook among Malaysian users and underscore the need for greater efforts to counteract hate speech in Malaysia. The study suggests the importance of developing effective policies and interventions to address this issue based on the findings.
Keywords: Hate speech, Facebook, Malaysia, Regulation, Prevalence